2007
DOI: 10.1093/jac/dkl516
|View full text |Cite
|
Sign up to set email alerts
|

Saquinavir, nelfinavir and M8 pharmacokinetics following combined saquinavir, ritonavir and nelfinavir administration

Abstract: The co-administration of nelfinavir and saquinavir/ritonavir leads to unpredictable changes in concentrations of both drugs. It is unclear whether the increased concentrations of M8 are associated with a clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In prior pharmacokinetic studies, NFV was shown to interact with a myriad of drugs metabolized by the cytochrome P-450 group of enzymes. [34][35][36] Another limitation is the fact that we did not collect genotyping data; therefore, there is no information on possible protease inhibitor resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In prior pharmacokinetic studies, NFV was shown to interact with a myriad of drugs metabolized by the cytochrome P-450 group of enzymes. [34][35][36] Another limitation is the fact that we did not collect genotyping data; therefore, there is no information on possible protease inhibitor resistance.…”
Section: Discussionmentioning
confidence: 99%